2012
DOI: 10.1186/1477-5956-10-55
|View full text |Cite
|
Sign up to set email alerts
|

Sequential depletion of human serum for the search of osteoarthritis biomarkers

Abstract: BackgroundThe field of biomarker discovery, development and application has been the subject of intense interest and activity, especially with the recent emergence of new technologies, such as proteomics-based approaches. In proteomics, search for biomarkers in biological fluids such as human serum is a challenging issue, mainly due to the high dynamic range of proteins present in these types of samples. Methods for reducing the content of most highly abundant proteins have been developed, including immunodepl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…The reduction of complexity can be performed by classical methods such as organic solvent solubilization and precipitation methods and by immuno depletion methods [3, 4]. …”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Smentioning
confidence: 99%
See 2 more Smart Citations
“…The reduction of complexity can be performed by classical methods such as organic solvent solubilization and precipitation methods and by immuno depletion methods [3, 4]. …”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Smentioning
confidence: 99%
“…The depletion of these HAPs allows the identification of low abundance proteins (LAPs) in proteomic analysis as well as the discovery of new biomarkers for diseases. The organic precipitation methods have been developed to reduce sample complexity by depletion of these HAPs in plasma using organic solvents such as acetonitrile, acetone, and trichloroacetic acid (TCA) [3, 4, 11-13]. …”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Smentioning
confidence: 99%
See 1 more Smart Citation
“…Widely used methods, such as immunodepletion for reducing the highly abundant proteins, have been applied; novel strategies are still developing. A recent study reported a method for pre-processing human serum samples based on a chemical depletion method involving two sequential protein precipitation steps with acetonitrile and DTT, with a subsequent two-dimensional difference gel electrophoresis (2D-DIGE) analysis and MALDI-TOF/TOF analysis to identify OA biomarkers (Fernandez-Costa et al, 2012). Reproducibility was examined by technical and biological replicates.…”
Section: Proteomic Analysis Of Serum In Oamentioning
confidence: 99%
“…The IAC approaches have been routinely coupled with both global discovery and targeted verification for disease-biomarker related studies [114, 128], and the applications include pancreatic cancer [124], ovarian cancer [129, 130], breast cancer [131, 132], renal cancer [133], gastric cancer [134], prostate cancer [135, 136], osteoarthritis [137139], cardiovascular disease [120, 140], etc .…”
Section: Proteomic Applications Of Iac In Biofluidsmentioning
confidence: 99%